Clinicopathological differences between Bartonella and other bacterial endocarditis-related glomerulonephritis – our experience and a pooled analysis - Kitamura, Mineaki; Dasgupta, Alana; Henricks, Jonathan; Parikh, Samir V.; Nadasdy, Tibor; Clark, Edward; Bazan, Jose A.; Satoskar, Anjali A. (Frontiers in Nephrology, 2024)
Background: Although Staphylococcus aureus is the leading cause of acute infective endocarditis (IE) in adults, Bartonella spp. has concomitantly emerged as the leading cause of “blood culture-negative IE” (BCNE). Pre-disposing factors, clinical presentation and kidney biopsy findings in Bartonella IE-associated glomerulonephritis (GN) show subtle differences and some unique features relative to other bacterial infection-related GNs. We highlight these features along with key diagnostic clues and management approach in Bartonella IE-associated GN. Methods: We conducted a pooled analysis of 89 cases of Bartonella IE-associated GN (54 published case reports and case series; 18 published conference abstracts identified using an English literature search of several commonly used literature search modalities); and four unpublished cases from our institution. Results: Bartonella henselae and Bartonella quintana are the most commonly implicated species causing IE in humans. Subacute presentation, affecting damaged native and/or prosthetic heart valves, high titer anti-neutrophil cytoplasmic antibodies (ANCA), mainly proteinase-3 (PR-3) specificity, fastidious nature and lack of positive blood cultures of these Gram-negative bacilli, a higher frequency of focal glomerular crescents compared to other bacterial infection-related GNs are some of the salient features of Bartonella IE-associated GN. C3-dominant, but frequent C1q and IgM immunofluorescence staining is seen on biopsy. A “full-house” immunofluorescence staining pattern is also described but can be seen in IE –associated GN due to other bacteria as well. Non-specific generalized symptoms, cytopenia, heart failure and other organ damage due to embolic phenomena are the highlights on clinical presentation needing a multi-disciplinary approach for management. Awareness of the updated modified Duke criteria for IE, a high index of suspicion for underlying infection despite negative microbiologic cultures, history of exposure to animals, particularly infected cats, and use of send-out serologic tests for Bartonella spp. early in the course of management can help in early diagnosis and initiation of appropriate treatment. Conclusion: Diagnosis of IE-associated GN can be challenging particularly with BCNE. The number of Bartonella IE-associated GN cases in a single institution tends to be less than IE due to gram positive cocci, however Bartonella is currently the leading cause of BCNE. We provide a much-needed discussion on this topic.